(untitled) (El Taco en la Brea, 2018)
Three hypotheses are explored here: the close and long-lasting relationship between Argentine literary criticism and theory is not a local feature (although not universal, it is rather global); in Argentina, literary theory is taught but not written; «theory» is a replaceable name, which back in the 1900s we used in a tentative way to refer to a kind of thinking about certain contingencies where something that we still call «literature» is involved.